TINDAK TUTUR DIREKTIF PEDAGANG PAKAIAN DALAM BAHASA MANDAILING DI PASAR UJUNG GADING KABUPATEN PASAMAN BARAT - Leli Hermita; Agustina Agustina; Muhammad Ismail Nasution (Jurnal Bahasa dan Sastra, 2014)
This research is aimed to describe the types of directive speech act, the function of directive speech act, speaking strategy, and the context of directive speech act in Mandailing used by the clothes seller at a traditional market in Ujung Gading, West Pasaman. The type of this research is qualitative with descriptive method. The technique used in data collecting is by recording and making a note about speech phenomenon in Mandailing used by the clothes seller at a traditional market in Ujung Gading, West Pasaman. Based on the research result and the study, can be concluded that as following. First, there are five types of directive speech act used by the clothes seller: (a) advising speech act, (b) permitting speech act, (c) preventing speech act, (d) begging speech act, and (e) commanding speech act. Second, there are five functions of directive speech act used by the clothes seller: (a) competitive, the locution purpose competes with the social purpose, (b) convivial, the locution purpose equals to the social purpose, (c) collaborative, the locution purpose ignores the social purpose, and (d) conflictive, the locution purpose opposites to the social purpose. Third, there are four speech strategies: (a) speech frankly without any conventionality, (b) speech by conventionality with a positive politeness, (c) speech by conventionality with a negative politeness, and (d) speech obscurely.